PERAN TEKNOLOGI INFORMASI DALAM MANAJEMEN KEUANGAN KORPORASI MODERN - Rina Apriliani (Prosiding Seminar Nasional Indonesia, 2024)
In the modern corporate era characterized by rapid business dynamics and tight competition, the role of information technology in corporate financial management has become extremely significant. This article discusses the key role played by information technology in the context of corporate financial management. Information technology has brought about fundamental changes in the way companies manage, process, and analyze financial data. Moreover, the presence of information technology has increased the operational efficiency of companies by automating financial tasks, providing faster and more accurate access to financial data, and enabling deeper data analysis. Furthermore, information technology also has played an important role in managing financial risks, ensuring compliance with increasingly strict regulations, and providing better customer service.